CREATIVITY AND ENTREPRENEURSHIP. METHODS OF STIMULATING CREATIVITY - Maria Irina Dromereschi (Studies and Scientific Researches: Economics Edition, 2016)
Creativity as producing new information system, you can put in what seems unconnected connection, after so many forms of the unfold plan and in content. An entrepreneur will think and do new things or old things in a new form trying to transform ideas into tangible things, products and services. Entrepreneurship is the process through which all functions, activities and actions are shared to identify business opportunities and creating organizations through which they will be used in order to obtain profit and meeting social interests. Boosting creativity is justified in that creative activity is educated, even if some native elements have their own importance in the creative process. If we start from the idea that most barriers to creative thinking are all human creations, tributaries of the left hemisphere, will have to find alternative responses to stimulation, shaping and maintaining the creative process and even create organizational culture conducive to the creative process. Ideas are our tenement dwellers and often are near us in the simplest and quickest form. Just educate us the activation process and instituting the ideas process which involves methods fall under three broad categories: imaginative, heuristics and logical approach. Subject to the risk taken, the combination of these methods can provide as many alternatives to a reality whose details they ultimately determines who assumes the risk of their own decisions.